A framework of trust in service workflows - Viriyasitavat, W (2013)
The everything as a service concept enables dynamic resource provisions to be seen and delivered as services. Their proliferation nowadays leads to the creation of new value-added services composed of several sub-services in a pre-specified manner, known as service workflows. The use of service workflow appears in various domains, ranging from the basic interactions found in several e-commerce and several online interactions to the complex ones such as Virtual Organizations, Grids, and Cloud Computing. However, the dynamic nature in open environments makes a workflow constantly changing, to be adaptable to the change of new circumstances. How to determine suitable services has becomes a very important challenge. Requirements from both workflow owners and service providers play a significant role in the process of service acquisition, composition, and interoperations. From the workflow owner viewpoint, requirements can specify properties of services to be acquired for tasks in a workflow. On the other hand, requirements from service providers affect trust-based decision in workflow participation. The lack of formal languages to specify these requirements poses difficulties in the success of service collaborations in a workflow. It impedes: (1) workflow scalability that tends to be limited within a certain set of trusted domains; (2) dynamicity when each service acts in an autonomous and unpredictable manner where any change might affect existing requirements; and (3) inconsistency in dealing with the disparate representations of requirements, causing high overhead for compliance checking. This thesis focuses on developing a framework to overcome, or at least alleviate, these problems. It situates in inter-disciplinary areas including logics, workflow modelling, specification languages, trust management, decision support system, and compliance checking. Two core elements are proposed: (1) a formal logic-based requirement specification language, namely Trust Specification (TS), such that the requirements can be formally and uniformly expressed; and (2) compliance checking algorithms to automatically check for the compliance of requirements in service workflows. It is worth noting that this thesis contains some proofs of logic extension, workflow modelling, specification language, and compliance checking algorithms. These might raise a concern to people focusing deep on one particular area such as logics, or workflow modelling who might overlook the essence of the work, for example (1) the application of a formal specification language to the exclusive characteristics of service workflows, and (2) bridging the gap of the high level languages such as trust management down to the lower logic-based ones. The first contribution of the framework is to allow requirements to be independently and consistently expressed by each party where the workflow participation decision and acquisition are subject to the compliance of requirements. To increase scalability in large-scale interoperations, the second contribution centres on automatic compliance checking where TS language and compliance checking algorithms are two key components. The last contribution focuses on dynamicity. The framework allows each party to modify existing requirements and the compliance checking would be automatically activated to check for further compliance. As a result, it is anticipated that the solution will encourage the proliferation of service provisions and consumption over the Internet.